Testing the importance of search frictions and matching through a randomized experiment in Jordan - Matthew Groh; David McKenzie; Nour Shammout; Tara Vishwanath (IZA Journal of Labor Economics, 2015)
We test the role of search and matching frictions in explaining the high unemployment of tertiary-educated youth in Jordan through a randomized experiment. Firms and job candidates were provided with a job-matching service based on educational backgrounds and psychometric assessments. Although more than 1,000 matches were made, youth rejected the opportunity of an interview in 28 percent of cases, and when a job offer was received, they rejected this offer or quickly quit the job 83 percent of the time. The results suggest voluntary unemployment in this context arises from preferences over non-wage job attributes.
Keywords: O12; O15; J64; J08; 330; Psychometrics; Labor market matching; Reservation utility; Youth unemployment; Jordan; Randomized experiment